Controlling Measures for Cost Overrun Causes in Highway Projects of Sindh Province - Sohu, S.; Abdullah, A. H.; Nagapan, S.; Rind, T. A.; Jhatial, A. A. (Engineering, Technology & Applied Science Research, 2019)
Cost overrun is a serious issue in the construction industry worldwide, including Pakistan. Cost overrun is a critical and serious issue found in highway projects among all construction projects in Pakistan. Cost overrun occurs when the final cost of the projects exceeds the actual cost of the project. The main objective of this research is to identify the main causes of cost overrun and to determine possible mitigation measures of the identified main causes of cost overrun from contractors of highway/road projects of Pakistan. In this study, a mixed mode (quantitative and qualitative) approach was used. A deep literature review helped to identify the 30 most common causes of cost overrun in the construction industry. In the first stage, a questionnaire was developed, and a survey was carried out among professional and experts who were working with contractors in highway projects. In the second stage, a semi-structured questionnaire was developed, and a survey was carried out to determine the possible mitigation measures of the identified main causes of cost overrun. Collected data for the first stage from experts were inserted in SPSS and were analyzed by using the average index method and the data of the second stage were analyzed by content analysis. It is expected that the findings of this research will be useful and helpful for the construction stakeholders to control and mitigate the major causes of cost overrun.